Development of bryophyta modules based on moss diversity in the Mandiangin tropical rainforest biodiversity park, South Kalimantan - Noorsalamiah Noorsalamiah; Aulia Ajizah; Sri Amintarti (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
This study was motivated by the limited availability of contextual and locally-based biology teaching materials, particularly on the topic of mosses (Bryophyta), which requires high conceptual and visualization skills. This study aims to develop and test the feasibility and practicality of a locally-based biology learning module on Bryophyta for 10th grade high school students. The research method used the Four-D (Define, Design, Develop, and Disseminate) development model from Thiagarajan et al. Data collection was carried out through field exploration of the diversity of moss species in the Mandiangin Tropical Rainforest Biodiversity Park, South Kalimantan, followed by validity testing by experts and practicality testing by students. The validation results by two expert lecturers showed that the module was highly valid with an average score of 93.06%, covering aspects of content feasibility, language, and presentation. Meanwhile, the practicality test obtained an average score of 87.56% with a highly practical category. These results indicate that the developed module is feasible, interesting, and effective in helping students understand the concept of Bryophyta through real examples from the surrounding environment. The integration of local potential in the module also supports contextual learning and strengthens students' ecological literacy. This module contributes to the enrichment of local potential-based biology learning resources and can be used by teachers as an alternative innovative teaching material for independent learning. Further research is recommended to integrate digital technology and test the effectiveness of the module in improving student learning outcomes, critical thinking skills, and environmental awareness. Abstrak. Penelitian ini dilatarbelakangi oleh masih terbatasnya ketersediaan bahan ajar biologi yang kontekstual dan berbasis potensi lokal, khususnya pada topik tumbuhan lumut (Bryophyta) yang menuntut kemampuan konseptual dan visualisasi tinggi. Penelitian ini bertujuan untuk mengembangkan serta menguji kelayakan dan kepraktisan modul pembelajaran biologi berbasis potensi lokal pada materi Bryophyta untuk peserta didik kelas X SMA. Metode penelitian menggunakan model pengembangan Four-D (Define, Design, Develop, dan Disseminate) dari Thiagarajan et al. Pengumpulan data dilakukan melalui eksplorasi lapangan terhadap keanekaragaman jenis lumut di Taman Keanekaragaman Hayati Hutan Hujan Tropis Mandiangin, Kalimantan Selatan, dilanjutkan dengan uji validitas oleh ahli dan uji kepraktisan oleh peserta didik. Hasil validasi oleh dua dosen ahli menunjukkan kategori sangat valid dengan skor rata-rata 93,06%, meliputi aspek kelayakan isi, kebahasaan, dan penyajian. Sementara itu, uji kepraktisan memperoleh skor rata-rata 87,56% dengan kategori sangat praktis. Hasil ini menunjukkan bahwa modul yang dikembangkan layak, menarik, dan efektif dalam membantu peserta didik memahami konsep Bryophyta melalui contoh nyata dari lingkungan sekitar. Integrasi potensi lokal dalam modul juga mendukung pembelajaran kontekstual dan memperkuat literasi ekologis siswa. Modul ini berkontribusi terhadap pengayaan sumber belajar biologi berbasis potensi lokal dan dapat digunakan guru sebagai alternatif bahan ajar inovatif untuk pembelajaran mandiri. Penelitian lanjutan disarankan untuk mengintegrasikan teknologi digital serta menguji efektivitas modul terhadap peningkatan hasil belajar, keterampilan berpikir kritis, dan kesadaran lingkungan peserta didik.